Structure of Cost of Equity as the Dependence on the Corporate- and Market Life Cycle - Konečný, Zdeněk (Vysoké učení technické v Brně, Fakulta podnikatelská, 2012)
Purpose of the article: Companies, like all living creatures, goes through their life cycle, which includes some partial phases. Each of these phases is specific. Depending up the corporate life cycle, there are changed managerial decisions, that have an considerable influence, among others, on financial indicators like liquidity (current ratio, quick ratio, cash ratio), return (on investment, assets, equity, sales), economic value added, or cost of capital. The purpose of this article is to show relations between corporate life cycle and the structure of cost of equity. Furthermore, there will be, besides the corporate life cycle, considered also the market life cycle and market positions, that can companies hold on the market, on which they are acting. Methodology/methods: There is used a method, based on the analysis of secondary data, gotten from financial statements of selected companies and from statistical and analytical documents, published by Czech Ministry of Industry and Trade. There are selected 39 companies, acting on the czech market with motor vehicles production. The data are gathered for periods from 2002 up to 2010. There is used a model by Reiners (2004) to identify phases of corporate- and market life cycle and market positions. For finding out the structure of cost of equity there is used the constructional model by Czech Ministry of Industry and Trade. Scientific aim: The selected companies are divided into groups with considering different phases of their life cycle and with considering their different market positions. There are for each period found out numbers of companies from these groups, that reached the minimal value, the value within the interval and maximal value of all risk rewards, that are, besides the riskless rate, components of cost of equity. Findings: The greatest part of cost of equity, reached on the market, is the riskless rate. Other components (and their shares on the cost of equity, reached on the market) except risk reward to size of the company were increasing mostly since 2007. By researching the structure of cost of equity in the case of selected companies, there were found out only small differences between companies in different phases of their life cycle and only small differences between companies, that hold different market positions. Conclusions: There are some limits connected with these findings. The constructional model for cost of equity calculation was developed for czech firms, so the generalizing for foreign companies and markets is limited. And the model by Reiners (2004) can identify phases of corporate- and market life cycle only using the interyear comparison of quantities, that are involved in the growth indicator, and furthermore, there isn’t possible to identify corporate- and market foundation.
Keywords: constructional model; corporate life cycle; cost of equity; market life cycle; market positions; risk rewards